Pur-Alpha Induces JCV Gene Expression and Viral Replication by Suppressing SRSF1 in Glial Cells. - Ilker Kudret Sariyer; Rahsan Sariyer; Jessica Otte; Jennifer Gordon (PLoS ONE, 2016)
OBJECTIVE:PML is a rare and fatal demyelinating disease of the CNS caused by the human polyomavirus, JC virus (JCV), which occurs in AIDS patients and those on immunosuppressive monoclonal antibody therapies (mAbs). We sought to identify mechanisms that could stimulate reactivation of JCV in a cell culture model system and targeted pathways which could affect early gene transcription and JCV T-antigen production, which are key steps of the viral life cycle for blocking reactivation of JCV. Two important regulatory partners we have previously identified for T-antigen include Pur-alpha and SRSF1 (SF2/ASF). SRSF1, an alternative splicing factor, is a potential regulator of JCV whose overexpression in glial cells strongly suppresses viral gene expression and replication. Pur-alpha has been most extensively characterized as a sequence-specific DNA- and RNA-binding protein which directs both viral gene transcription and mRNA translation, and is a potent inducer of the JCV early promoter through binding to T-antigen. METHODS AND RESULTS:Pur-alpha and SRSF1 both act directly as transcriptional regulators of the JCV promoter and here we have observed that Pur-alpha is capable of ameliorating SRSF1-mediated suppression of JCV gene expression and viral replication. Interestingly, Pur-alpha exerted its effect by suppressing SRSF1 at both the protein and mRNA levels in glial cells suggesting this effect can occur independent of T-antigen. Pur-alpha and SRSF1 were both localized to oligodendrocyte inclusion bodies by immunohistochemistry in brain sections from patients with HIV-1 associated PML. Interestingly, inclusion bodies were typically positive for either Pur-alpha or SRSF1, though some cells appeared to be positive for both proteins. CONCLUSIONS:Taken together, these results indicate the presence of an antagonistic interaction between these two proteins in regulating of JCV gene expression and viral replication and suggests that they play an important role during viral reactivation leading to development of PML.